Corporality: From Commonality to Structurality - Koss, Andrey (Ukrainian Cultural Center, 2024)
The article conducts a philosophical and ethical investigation into the interaction between human corporeality and the technologies that transform it. As the focus on these technologies shifts, the understanding of the model of corporeality changes as well. An analysis of historical teachings about the essence of corporeality and its structural components is carried out, allowing for the determination of the limits of changes that do not distort human nature. The relationship between corporeality and spirituality in various philosophical traditions and spiritual practices is also examined. The contribution of Rene Descartes to the doctrine of corporeality is highlighted, as he approached this duality from a new perspective, using analytical methods to identify patterns in the existence of the bodily and the spiritual. He concluded that matter has the property of divisibility, while spirituality is indivisible. Corporeality has structural elements, whereas the spiritual does not possess such characteristics, which allowed for a reevaluation of corporeality and the application of a new methodology for study. Over time, structurality began to transform into functionality as an expression of corporeality. This led to the formation of doctrines, one of which viewed humans as functioning soulless machines (block-functional model), while another approach contributed to the emergence of cellular theory (ontogenetic-epistemological), as one of the key directions in the study of human corporeality. The article examines the views on corporeality of Plato and Aristotle, focusing on their interpretation of the model of the immortality of the soul after physical death. It reveals the connections between body and spirit in the models of G.-W.-F. Hegel (the concept of interiorization) and F.-W. Nietzsche (the formation of the soul). The perspectives on corporeality by J. Baudrillard ("differentiated prosthesis", "matrix of simulation", "body as an object of fetishiza tion") and the socio-cultural constructions of corporeality in the teachings of J.-P. Sartre, E.-G.-A. Husserl, and M. Merleau-Ponty are also discussed. Additionally, a philosophical analy sis of the understanding of immortality is conducted. The article examines the influence of neuroscience on cognitive activity and bodily experiences, the expansion of embodiment beyond the physical body, CRISPR technologies, and the impact of virtual reality on existentialism. У статті проводиться філософсько-етичне дослідження взаємодії між людською тілесністю та технологіями, які її трансформують. Залежно від зміни фокуса розглянутих технологій змінюється розуміння моделі тілесності. Проводиться аналіз історичних учень про сутність тілесності та її структурні компоненти, що дозволяє визначити межі змін, які не змінюють людську природу. Розглядається зв’язок тілесності та духовності в різних філософських традиціях і духовних практиках. Показано внесок у вчення про тілесність Рене Декарта, який підійшов до цієї дуальності з нового ракурсу, застосовуючи метод аналізу для виявлення закономірностей в існуванні тілесного і духовного. Він дійшов висновку, що матерія має властивість подільності, тоді як духовність – неподільна. Тілесність має структурні елементи, у той час як духовне не має подібної особливості, що дозволило по-новому розглянути тілесність і застосувати нову методологію дослідження. З часом структурність почала трансформуватися у функціональність як вираження тілесності. Це призвело до формування вчень, одне з яких розглядало людину як функціонуючу бездушну машину (блочно-функціональна модель), тоді як інший підхід сприяв виникненню клітинної теорії (онтогносеологічна) як одного з ключових напрямків вивчення людської тілесності. В статті розглядаються погляди на тілесність Платона та Аристотеля, їх трактування моделі безсмертя душі після фізичної смерті. Відкриваються взаємозв'язки між тілом і духом у моделях Г.-В.-Ф. Гегеля (концепція інтеріоризації) та Ф.-В. Ніцше (формування душі). Обговорюються погляди на тілесність Ж. Бодрійяра («диференційований протез», «матриця симуляції», «тіло як об'єкт фетишизації») та соціально-культурологічні конструкції тілесності у вченні Ж.-П. Сартра, Е.-Ґ.-А. Гуссерля та М. Мерло-Понті. Також проведено філософський аналіз розуміння безсмертя. Досліджується також вплив нейронаук на когнітивну активність і тілесні переживання, розширення тілесності за межі фізичного тіла, технології CRISPR, а також вплив віртуальної реальності на екзистенціалізм.
Тілесність: від цілісності до структурності
Keywords: body; mind; soul; models of corporeality; transhumanist technologies; тіло; розум; душа; моделі тілесності; трансгуманістичні технології